Evaluation of the mean platelet volume in patients with cardiac syndrome X (Clinics, 2012)
OBJECTIVE: Cardiac syndrome X is characterized by angina-lke chest pain, a positive stress test, and normal coronary arteries. A patient's mean platelet volume, which potentially reflects platelet function and activity, is associated with coronary atherosclerosis and endothelial dysfunction. The aim of the present study was to evaluate the mean platelet volumes of patients with cardiac syndrome X, those with coronary artery disease and normal subjects. METHODS: Two hundred thirty-six subjects (76 patients with cardiac syndrome X, 78 patients with coronary artery disease, and 82 controls) were enrolled in the study. All of the subjects were evaluated with a detailed medical history, physical examination, and biochemical analyses. The mean platelet volumes were compared between the three groups. RESULTS: The mean platelet volumes in the patients with cardiac syndrome X and with coronary artery disease were significantly higher than those that were observed in the control group. There were no significant differences in the mean platelet volumes between the cardiac syndrome X and the coronary artery disease groups. CONCLUSION: We have established that patients with cardiac syndrome X and coronary artery disease exhibit higher mean platelet volumes compared to controls. Patients with cardiac syndrome X exhibited higher mean platelet volumes compared to the controls, reflecting the presence of subclinical atherosclerosis. These findings suggest that, in addition to endothelial dysfunction, the presence of atherosclerosis may also contribute to the etiopathogenesis of cardiac syndrome X.